Particulate Inorganic Carbon (PIC) and associated coccospheres and detached coccoliths in waters off the Southeast Pacific margin in 2015 - Francisco Díaz-Rosas; Cristian A Vargas; Peter von Dassow (PANGAEA, 2025)
This dataset consist of Particulate Inorganic Carbon (PIC) and Particulate Organic Carbon (POC) measurements, as well as coccospheres and detached coccoliths counts across low oxygen and low pH waters off the Southeast Pacific margin. Two cruise were conducted between ~20°-35° S and 70°-73° W during the late-spring 2015 (LowpHOX 1, this dataset) and mid-summer 2018 (LowpHOX 2, https://doi.pangaea.de/10.1594/PANGAEA.975784). For the measurements of PIC, we followed a slightly modified version of the procedure introduced by Poulton et al. (2006). In summary, we filtered between 0.1-1.5 L of seawater (increasing with sampled depth) onto 25 mm polycarbonate filters with a 0.4 μm pore size. The filters were immediately rinsed with a squirt of potassium tetraborate solution in 2015 and with seawater alkalinized with ammonium in 2018 (to maintain pH > 8.0 while in storage) and stored in metal-free Falcon tubes at -20 C until transit to the lab. Subsequently, Ca2+ was extracted with nitric acid and quantified using Inductively Coupled Plasma Atomic Mass Spectrophotometry. A correction was made to correct for potential excess of Ca2+ due to Na+ residues that might be left on the filters. The analytical procedures for POC measurements are described in Vargas et al. (2021). For enumeration of coccospheres and detached coccoliths, between 0.1 to 1.0 L of seawater (increasing with depth) were filtered onto 25 mm polycarbonate filters with a 0.8 μm pore size, left to dry at room temperature in Petri dishes, and stored with desiccant until microscopy analyses. Total coccosphere counts were conducted on filter slide preparations with oil immersion, using cross-polarized light microscopy (Zeiss, Axioscope 5). The analysis of twenty field of view at 400x magnification covered 5.1 mm2 of the filter area, corresponding to a range of 1.9-16.3 mL of seawater analysed. For counts of total detached coccoliths, eleven fields of view per filter were screened (224 x 165 μm per frame) at 630x magnification (oil immersion objective), covering 0.41 mm2 of the filter area, corresponding to total volumes of 0.2-1.3 mL of seawater analysed. An issue arose where the filters from inshore-offshore 2015 sampling (20 S; Stations T1-T6) exhibited excessive brightness under cross-polarized light microscopy, for which counts were made through scanning electron microscopy (SEM) analysis (Quanta FEG 250) as described in Díaz-Rosas et al. (2021). For the quantification of coccosphere abundances (see equation in Díaz-Rosas et al., 2021), between 28-48 images taken at 800-1500x magnification were examined per filter, covering from 5 to 6 mm2 of the filter area corresponding to a range of 2.1-18.4 mL of seawater analyzed. For total detached coccolith abundances, between 4-5 images were examined per filter, covering from 0.6 to 1.0 mm2 of the filter area corresponding to a range of 0.2-2.8 mL of seawater analyzed. PIC measurements and coccoliths densities were used to assess the proposition by Hofmann and Schellnhuber 2009 that ocean acidification decreases coccolithophore-produced PIC pools, leading to weakened sinking of Particulate Organic Carbon to deeper waters, which may influence the depth of organic matter remineralization and subsurface oxygen levels.